Reflections on limitations to access to justice for maintenance creditors in Jalisco, Mexico - Rojas Maldonado, Natasha Ekaterina; Orozco González, Wilberth; Pelayo Torres, Jetsabel Anahi; Del Castillo Martínez, Arely Alejandra (Scientific journal of social studies, 2025)
This mixed and descriptive study highlights the problems faced by creditors and representatives in the processing of maintenance proceedings, reflects the difficulties faced by the actors involved in the proceedings and their limited access to justice.
Keywords: Maintenance; maintenance obligation; access to justice